Evaluating Growth Patterns and Soil Dynamics of the Endangered African Rosewood (Pterocarpus erinaceus Poir.) in Contrasting Ecological Regions in Ghana - Michael Asigbaase; Daniel Adusu; Daniel Akoto Sarfo; Collins Ayine Nsor; Samuel Kumi; Seidu Adams; Paul Kofi Nsiah; Selina Adutwumwaa Acheamfour (International Journal of Forestry Research, 2024)
Pterocarpus erinaceus (Poir.) is an endemic and endangered species of the Guinea-Sudano-Sahelian​ zones currently overexploited for timber, fodder, and medicinal purposes. Therefore, plantations are critical to meeting the high demand in the international market while reducing pressure on natural stands, but its growth performance across different ecological zones is not well documented. Thus, we assessed the influence of ecological zones and soil properties on the survival and growth performance of P. erinaceus. Data were collected from 12 subplots of P. erinaceus stands in the Dry Semi-Deciduous Fire Zone (DSFZ) and 16 subplots in the Moist Semi-Deciduous North West Zone (MSNW). We assessed the survival and growth performance of P. erinaceus using one-way ANOVA, variation in soil properties using the Generalized Linear Model, and the influence of soil properties on P. erinaceus growth characteristics via correlation analysis. We found that the percentage survival of P. erinaceus was similar in both ecological zones. However, P. erinaceus demonstrated a high level of variation in growth attributes, growing taller with deeper canopies in wetter conditions and larger crown spread in drier conditions. The aboveground biomass carbon stocks of P. erinaceus stands were similar in both ecological zones, highlighting the potential role of the species as a carbon sink in the ecological zones. Soil organic matter, nitrogen, and calcium contents were higher in soils of the MSNW stands than those of the DSFZ stands. However, potassium, magnesium, sodium, and phosphorus contents were stable across the ecological zones. We concluded that wetter conditions enhance the growth performance of P. erinaceus as a timber species.